Stability of Reconstituted Telavancin Drug Product in Frozen Intravenous Bags. Issue 7 (July 2015) - Gu, Zhengtian; Wong, Anissa; Raquinio, Elvira; Nguyen, Alice
Background and Objective: Intravenous (IV) infusions of telavancin for injection are generally administered in-hospital, but in some circumstances they may be administered in an outpatient environment. In that setting, antibiotics may be premixed and frozen. This study determined the chemical stability of nonpreserved telavancin in various commonly used reconstitution diluents stored in IV bags (polyvinyl chloride [PVC] and PVC-free) at −20°C (-4°F) without light. Methods: Telavancin (750 mg/vial) was reconstituted with 5% dextrose injection USP (D5W) or 0.9% sodium chloride injection USP (NS) to obtain drug solutions at approximately 15 mg/mL. Infusion solutions of telavancin at diluted concentrations of 0.6 mg/mL and 8.0 mg/mL covering the range utilized in clinical practice were prepared in both PVC and PVC-free IV bags using D5W or NS solutions. The infusion solutions were stored under frozen conditions (-20°C ± 5°C [-4°F ± 41°F]) and the chemical stability was evaluated for up to 32 days. Telavancin concentration, purity, and degradant levels were determined using a stability-indicating high-performance liquid chromatography (HPLC) method. Results: Telavancin IV infusion solutions in D5W or NS at 0.6 mg/mL and 8 mg/mL and stored at −20°C (-4°F) met the chemical stability criteria when tested on days 0, 7, 14, and 32. The assayed telavancin concentration at each time point was within 97% to 103% of the initial mean assay value. The total degradants quantified by the HPLC stability-indicating method did not show any significant change over the 32-day study period. Conclusion: Telavancin IV infusion solutions (in D5W or NS) in both PVC and PVC-free IV bags were stable for at least 32 days when stored at −20°C (-4°F) without light. These results provide prolonged frozen stability data further to that previously established for 7 days under refrigerated conditions (2°C-8°C [36°F −46°F]), and for 12 hours at room temperature when diluted into IV bags containing D5W, NS, or lactated Ringer's solution.